2010
DOI: 10.18195/issn.0312-3162.25(4).2010.399-440
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of divergent embryonic and larval development in the Australian frog genus Geocrinia (Anura: Myobatrachidae)

Abstract: -Embryonic and larval development of the seven Geocrinia species across Australia are described and compared. This Australian myobatrachid genus includes three species with terrestrial embryonic development followed by aquatic exotrophic larval development and four species with entirely terrestrial and endotrophic development. Comparisons are made among species within the terrestrial/exotrophic group and the endotrophic group, and between the two breeding modes of each different species-group. Morphological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Moler, 1985), Crinia, Geocrinia (Myobatrachidae; e.g. Doughty, Anstis & Price, 2009;Anstis, 2010), and Boophis (Mantellidae; e.g. Randrianiaina et al, 2009), requires detailed ontogenetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moler, 1985), Crinia, Geocrinia (Myobatrachidae; e.g. Doughty, Anstis & Price, 2009;Anstis, 2010), and Boophis (Mantellidae; e.g. Randrianiaina et al, 2009), requires detailed ontogenetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…This low dispersal is evident from genetic studies that showed almost no gene flow between populations (Driscoll 1998a). As the species are specialised terrestrial breeders with entirely endotrophic (non-feeding) development (Mitchell 2001;Anstis 2010), their lifecycle is completed in and immediately adjacent to breeding sites. Breeding sites are vulnerable to extremes of flooding and desiccation, as eggs develop in moist soils but cannot be submerged (Wardell-Johnson and Roberts 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The breeding season commences in late winter/early spring (August/September) and continues into summer (December/January) ( Driscoll, 1998 ). Eggs are laid in a shallow depression in moist soil adjacent to ephemeral streams and develop endotrophically until metamorphosis is completed between November and January ( Anstis, 2010 ). Geocrinia vitellina is a closely related species with an allopatric distribution, occurring ~6 km to the east.…”
Section: Methodsmentioning
confidence: 99%
“…Development times were calculated as the average number of days from stage 19 to stage 39 according to developmental stages defined in Anstis (2010) for Geocrinia species. Stage 19 (hind limb buds just visible) was the earliest stage that all embryos were collected at, and stage 39 was just prior to metamorphosis (tail stub < 2 mm), when metamorphs are routinely transferred to different terraria, according to Perth Zoo husbandry practices.…”
Section: Methodsmentioning
confidence: 99%